2004
DOI: 10.1177/0192513x03257715
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Economic Policies and Employment Assistance Programs on the Well-Being of Displaced Female Apparel Workers

Abstract: This article explores howlabor market trends and current employment assistance policies affect reemployment opportunities and emotional well-being in a sample of female dislocated apparelworkers. The study follows the displacedwomen from the time the plant closed for 6 months to assess their financial and emotional well-being as they reentered the job market or enrolled in training programs. Averagewages of the reemployedwomen were less than their former plantwage; 14% lost their health insurance, and only hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Relating this to public policy, Campara et al (2017) found that, even if small governmental cash transfers generally increased subjective well-being for poor Brazilian families, this was not sufficient to eliminate individuals' general negative perceptions of their household's economic situation. Other studies that examined individuals' perceptions of their household finances also uncovered a positive relationship with specific facets of subjective well-being like self-esteem (Krause et al 1991) or low levels of depression (Rocha and Strand 2004). These claims build on Bovi (2009), who stated that consumer confidence illustrates information about feelings, as it reflects the moods of citizens and frequently contains heuristic and biased responses.…”
Section: Perceptions Of Economic Conditions and Subjective Well-beingmentioning
confidence: 98%
“…Relating this to public policy, Campara et al (2017) found that, even if small governmental cash transfers generally increased subjective well-being for poor Brazilian families, this was not sufficient to eliminate individuals' general negative perceptions of their household's economic situation. Other studies that examined individuals' perceptions of their household finances also uncovered a positive relationship with specific facets of subjective well-being like self-esteem (Krause et al 1991) or low levels of depression (Rocha and Strand 2004). These claims build on Bovi (2009), who stated that consumer confidence illustrates information about feelings, as it reflects the moods of citizens and frequently contains heuristic and biased responses.…”
Section: Perceptions Of Economic Conditions and Subjective Well-beingmentioning
confidence: 98%
“…Researchers including Eberts (2005), Grubb (1996), Lazenson (2004), Feser (2003), Hamm (2004), Harkin (2003), and Herman (1999) have conducted research on the benefits of education and training and the need for appropriate assessment and career planning (Bowl, 2001;Flint & Frey, 2001;Jacobson, LaLonde & Sullivan, 2005;Kasworm, 2003;Kilgore, 2003;Ranney & Betancur, 1992;Rocha & Strand, 2004) in order for individuals to be successful in their education and the role community colleges play in enhancing economic well being. Research has also addressed the need for skills in 21st century if the United States is to remain competitive in the global economy (Grubb, 1996;Hamm, 2004;Harkin, 2003;Malo, 2003;Porter, 1990).…”
Section: Literature Review Introductionmentioning
confidence: 99%